2000
DOI: 10.1007/s004410000238
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytosis of dying chondrocytes by osteoclasts in the mouse growth plate as demonstrated by annexin-V labelling

Abstract: Endochondral ossification in the epiphyseal growth plate of long bones is associated with programmed cell death (PCD) of a major portion of the chondrocytes. Here we tested the hypothesis that at the ossification front of the epiphyseal growth plate osteoclasts preferentially phagocytose chondrocytes that are undergoing PCD. We injected biotin-labelled annexin-V (anx-V-biotin, an early marker of PCD) intravenously in young adult mice. After 30 min of labelling, long bones were recovered and the tissue distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 27 publications
1
18
1
Order By: Relevance
“…Fig. 6C demonstrated that OCs indeed removed apoptotic and dying myeloma cells by phagocytosis, confirming previous reports (37,38). The phagocytic activity of OCs did not affect their viability or their ability to support myeloma cell growth and survival.…”
Section: Resultssupporting
confidence: 88%
“…Fig. 6C demonstrated that OCs indeed removed apoptotic and dying myeloma cells by phagocytosis, confirming previous reports (37,38). The phagocytic activity of OCs did not affect their viability or their ability to support myeloma cell growth and survival.…”
Section: Resultssupporting
confidence: 88%
“…Evidence that osteoclastic attack is directed toward apoptotic osteocytes has been reported in the growing skeleton in relation to bone renewal [44], and under pathologic conditions [45,46]. Similar to macrophages, osteoclasts are attracted to apoptotic cells that expose phosphatidylserine on their outer cell surface at an early stage of apoptosis [47]. In the case of osteoclasts, the apoptotic cells that attract them are osteocytes and hypertrophic chondrocytes of the growth plate [47].…”
Section: Strain-dependent Regulation Of Osteoclast Activity During Bomentioning
confidence: 97%
“…Similar to macrophages, osteoclasts are attracted to apoptotic cells that expose phosphatidylserine on their outer cell surface at an early stage of apoptosis [47]. In the case of osteoclasts, the apoptotic cells that attract them are osteocytes and hypertrophic chondrocytes of the growth plate [47]. Exposure of phosphatidylserine on osteocytic cell "fingers" in canaliculi abutting on the wall of the cutting cone might therefore be the signal that urges the osteoclasts to continue absorption in that direction.…”
Section: Strain-dependent Regulation Of Osteoclast Activity During Bomentioning
confidence: 98%
“…Chondrocytes of the human growth plate experience a life cycle that ranges from resting to proliferating before becoming hypertrophic cells and finally undergoing programmed cell death (Ballock and O'Keefe 2003;Forriol and Shapiro 2005;Shum and Nuckolls 2002), with their apoptotic bodies supposedly being phagocytosed by osteoclasts (Bronckers et al 2000). Until now, opinions regarding the ultimate fate of terminally differentiated hypertrophic chondrocytes have been conflicting.…”
Section: Fate Of Hypertrophic Chondrocytesmentioning
confidence: 99%